miR-514a promotes neuronal development in human iPSC-derived neurons - Akaba, Yuichi; Takahashi, Satoru; Suzuki, Keiichiro; Kosaki, Kenjiro; Tsujimura, Keita (Frontiers in Cell and Developmental Biology, 2023)
Proper development and function of the central nervous system require precise regulation of gene expression. MicroRNAs (miRNAs), a group of small non-coding RNAs that can negatively regulate gene expression at the post-transcriptional level, are critical regulators of neuronal development, and dysregulation of microRNAs has been implicated in various neurological disorders. Changes in microRNA expression and repertoire are related to the emergence of social and behavioral variations in closely related primates, including humans, during evolution. MicroRNA-514a (miR-514a) is an X-linked miRNA that is conserved in species with higher social and cognitive functions, and frequent tandem duplications of miR-514a have been found in primate genomes. Here, we demonstrate that miR-514a plays a crucial role in neuronal development in neurons derived from human induced pluripotent stem cells (iPSCs). Overexpression of miR-514a increased dendritic length, soma size, and activity levels of mammalian target of rapamycin (mTOR) signaling in induced pluripotent stem cell-derived neurons, whereas blocking of endogenous miR-514a inhibited neuronal development. Furthermore, we performed a functional analysis of the miR-514a variation found during primate evolution, to investigate the impact of miR-514a sequence variation and associated changes in expression on brain development during evolution. We found that mutation in miR-514a significantly reduced the expression of the mature form and abolished the effects observed when native miR-514a was expressed. Our findings provide new insights into the functional role of miR-514a in the regulation of neuronal development and evolution of primate brain development.